Locally Advanced Laryngeal/ Hypopharynx Carcinoma: Organ Preservation Protocol! - Peixoto, Conceição (2015)
Objective: Understand the role of organ preservation protocol in locally advanced laryngeal/ hypopharynx carcinoma, as well as, to be able to found out predictive factors.Study design: RetrospectiveMaterial and Methods: The study selected all the patients treated between 2004 and 2009. All patients began treatment with induction chemotherapy followed by radiotherapy and concomitant or subsequent chemotherapy. The results were analyzed by clinical and image evaluation.Results: The study included 43 patients with a mean age of 55 years, 97.7% were male. 65.6% respond to the induction chemotherapy, being influenced by the type of chemotherapy used. Local or regional recurrence occurred in 23.3%. Overall survival was 65% at 1 year, 44% at 3 years and 35% at 5 years. Age (p = 0.026) and tumor size (T) (p = 0.020) appear to influence overall survival.Conclusion: The study showed that chemotherapy followed by concurrent radiochemotherapy is a valid alternative to surgery in locally advanced tumors of the larynx.